Comparing concussion rates as reported by hockey Canada with head contact events as observed across minor ice-hockey age categories. (July 2020) - Robidoux, Michael A; Kendall, Marshall; Laflamme, Yannick; Post, Andrew; Karton, Clara; Hoshizaki, T Blaine
Head injuries in elite and youth sport have garnered growing public attention in part because of high-profile cases of professional athletes suffering career-ending/threatening concussions and because of the increase in medical studies identifying how repeated concussive events can lead to long-term health problems, most notably degenerative brain disease. Public concerns around youth ice hockey are intensifying in light of recent evidence which suggests that effects of head injury are worse for youth than they are for athletes in later stages of life. To better understand concussion injury rate trends across all levels of youth hockey, this paper provides a retrospective analysis of concussion related hockey injury as recorded in Hockey Canada's Injury Reporting System from the period covering 2009 to 2016, combined with two years of observational research documenting head contact events in minor hockey in the Ottawa and Gatineau regions of Ontario and Quebec. By comparing two different data sets through different methodological designs, it provides important insight into the levels of head contact in youth hockey, how head contact is occurring, and offers commentary about the levels of risk players are exposed to in minor hockey in Canada.